KARAKTERISTIK PERKEMBANGAN ANAK USIA 5-6 TAHUN DALAM ASPEK KOGNITIF MELALUI PERMAINAN BALOK - Mardianingsih, Mardianingsih; Azizah, Nuris (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2022)
This study aims to obtain information on the developmental characteristics of children aged 5-6 years in the cognitive aspect through block games at PAUD Al-Mardiyah Mekar Jaya, Pinang District, Tangerang City. PAUD Al-Mardiyah Mekar Jaya is located in the district of Pinang, Tangerang City, Banten Province. Established in 2010 and developing the